2023
DOI: 10.1186/s40659-023-00445-2
|View full text |Cite
|
Sign up to set email alerts
|

Topsoil and subsoil bacterial community assemblies across different drainage conditions in a mountain environment

Abstract: Background High mountainous environments are of particular interest as they play an essential role for life and human societies, while being environments which are highly vulnerable to climate change and land use intensification. Despite this, our knowledge of high mountain soils in South America and their microbial community structure is strikingly scarce, which is of more concern considering the large population that depends on the ecosystem services provided by these areas. Conversely, the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Soil bacterial diversity is known to be in uenced by changes in the environmental physico-chemical factors such as temperature, pH, water content, nutrients, texture, and vegetation types. ( (Mhete, et al 2020;Aguado-Norese, et al 2023). In this study, we observed high diversity and variation both within and across different treatment groups and depths, highlighting the complexity of the soil samples.…”
Section: Discussionmentioning
confidence: 55%
“…Soil bacterial diversity is known to be in uenced by changes in the environmental physico-chemical factors such as temperature, pH, water content, nutrients, texture, and vegetation types. ( (Mhete, et al 2020;Aguado-Norese, et al 2023). In this study, we observed high diversity and variation both within and across different treatment groups and depths, highlighting the complexity of the soil samples.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, soil microbial diversity can only be fully understood through the integration with these connected disciplines. Despite some efforts to combine soil microbial diversity and geochemical data (e.g., Mandakovic et al, 2018;Aponte et al, 2022;Barret et al, 2022;Aguado-Norese et al, 2023), integrated studies are scarce. As an example, in our survey the type of soil was rarely explicitly indicated, despite the great diversity of soil orders identified in Chile (Casanova et al, 2013).…”
Section: Collaborative Multi-and Interdisciplinary Studiesmentioning
confidence: 99%